Sosialisasi sains dan teknologi ICT di sekolah - Mustafa, , (2009)
The concept of sosialisation of science and technology implies that the process of acquiring skills and knowledge related to science and techonology is broader than the formal schooling process. It encompasses also the nonformal and informal processes at home, industries and through other agencies outside. A comprehensive study was conducted between 1996-1999 to describe the status of teaching and learning of science and technology related subjects, the role of teachers, infrastructural and material support in teaching and learning science and technology. On the basis of the finding of the study, certain recommendations were proposed. These in turn, could become the basis of a standard for socialisation of science and technology. Selected administrators and key personels in education, were asked to evaluate the proposed standard and make changes when necessary. Based on the feedback and the degree of consensus reached, final statements were selected to be included in the standard which encompassed the following five aspects; objective and content of curriculum, the process of teaching and learning, the role of teachers, the facilities, equipments and materials, and the involvement of agencies outside the school system. A standard on aspects of education could be used by various bodies because it provides a clear guidelineof the knowledge and skills that students have to acquire as well as the methods and equipment that teachers need to use. A standard provides a list of criteria which could be used to measure the quality of various activities conducted.